2016
DOI: 10.3748/wjg.v22.i45.10009
|View full text |Cite
|
Sign up to set email alerts
|

Heparin bridge therapy and post-polypectomy bleeding

Abstract: AIMTo identify risk factors for post-polypectomy bleeding (PPB), focusing on antithrombotic agents.METHODSThis was a case-control study based on medical records at a single center. PPB was defined as bleeding that occurred 6 h to 10 d after colonoscopic polypectomy and required endoscopic hemostasis. As risk factors for PPB, patient-related factors including anticoagulants, antiplatelets and heparin bridge therapy as well as polyp- and procedure-related factors were evaluated. All colonoscopic hot polypectomie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Eight articles were excluded after the fulllength review (five articles did not report the outcome of interest and three articles did not have participants with heparin-bridging therapy). Therefore, five studies (four retrospective cohort studies and one case-control study) [20][21][22][23][24] consisting of 2601 patients were included in the metaanalysis. File S2 outlines the search methodology and study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight articles were excluded after the fulllength review (five articles did not report the outcome of interest and three articles did not have participants with heparin-bridging therapy). Therefore, five studies (four retrospective cohort studies and one case-control study) [20][21][22][23][24] consisting of 2601 patients were included in the metaanalysis. File S2 outlines the search methodology and study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, five studies (four retrospective cohort studies and one case-control study) [20][21][22][23][24] consisting of 2601 patients were included in the metaanalysis. After the exclusion of 52 duplicated articles, 1386 articles underwent title and abstract review.…”
Section: T He Initial Search Yielded 1438 Potentially Rele-mentioning
confidence: 99%
“…In the Japan Gastroenterological Endoscopy Society guidelines, peri‐procedural heparin bridging therapy (HBT) is recommended in patients who have a high risk of thromboembolism after antithrombotic therapy is interrupted, because low‐molecular‐weight heparin is thought to be safe and effective on the treatment of venous thromboembolism . However, recent studies, including a nationwide multicenter survey, have indicated that HBT increases the risk of post‐procedural bleeding . The safety of HBT during endoscopic interventions is thus still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, recent studies, including a nationwide multicenter survey, have indicated that HBT increases the risk of post-procedural bleeding. [7][8][9] The safety of HBT during endoscopic interventions is thus still unclear. We aimed to evaluate peri-procedural HBT in patients taking anticoagulants who underwent colonic endoscopic mucosal resection (EMR).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the use of heparin as a bridge therapy alone cannot eliminate bleeding associated with polypectomy. A recent similar case-control study also demonstrated that an increased postpolypectomy bleeding incidence was observed regardless of antithrombotic agent discontinuation and use of heparin bridging therapy [11]. Therefore, careful assessment of individual risk before polypectomy is warranted.…”
mentioning
confidence: 99%